A combined scattering and diffraction model for elliptical hair rendering. (15th July 2021) - Benamira, Alexis; Pattanaik, Sumanta
Abstract: Realistic hair rendering relies on fiber scattering models. These models are based on either ray tracing or on full wave‐propagation through the hair fiber. Ray tracing can model most of the scattering phenomenon observed but misses the important effect of diffraction. Indeed human natural hair specific dimensions and geometry demands for the wave nature of light to be taken into consideration for accurate rendering. However, current full‐wave model requires nonpratical, several days precomputation, that needs to be repeated for every change in the hair geometry or color, for appropriate results. We present in this paper a dual hair scattering model which considers the dual aspect of light: as a wave and as a ray. Our model accurately simulates both diffraction and scattering phenomena without requiring any precomputation. Furthermore, it can simulate light transport in hairs of arbitrary elliptical cross‐sections. This new dual approach enables our model to significantly improve the appearance of rendered hair and qualitatively match scattering and diffraction effects seen in photos of real hair while adding little computation overhead.